2001
DOI: 10.1074/jbc.m105322200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Raf by Akt Controls Growth and Differentiation in Vascular Smooth Muscle Cells

Abstract: The stimulation of platelet-derived growth factor (PDGF) receptors shifts vascular smooth muscle (VSM) cells toward a more proliferative phenotype. Thrombin activates the same signaling cascades in VSM cells, namely the Ras/Raf/MEK/ERK and the phosphatidylinositol 3-kinase (PI 3-kinase)/Akt pathways. Nonetheless, thrombin was not mitogenic, but rather increased the expression of the smooth muscle-specific myosin heavy chain (SM-MHC) indicative of an in vitro re-differentiation of VSM cells. A more detailed ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
107
4
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(125 citation statements)
references
References 54 publications
(19 reference statements)
13
107
4
1
Order By: Relevance
“…It is interesting to speculate that VSMCs express low levels of the GPCR-coupled PI3K-␥ isoform or lack the appropriate repertoire of G proteins to activate PKC-␦-NF-B and PKC--GATA-2 pathways. In support of the former hypothesis, thrombin has been shown to induce only a weak and transient phosphorylation of Akt compared with PDGF in VSMC (65).…”
Section: Thrombin Fails To Induce Nf-b and Gata Binding To The Vcam-1mentioning
confidence: 57%
“…It is interesting to speculate that VSMCs express low levels of the GPCR-coupled PI3K-␥ isoform or lack the appropriate repertoire of G proteins to activate PKC-␦-NF-B and PKC--GATA-2 pathways. In support of the former hypothesis, thrombin has been shown to induce only a weak and transient phosphorylation of Akt compared with PDGF in VSMC (65).…”
Section: Thrombin Fails To Induce Nf-b and Gata Binding To The Vcam-1mentioning
confidence: 57%
“…This cross-talk inhibition of the Raf-MAPK pathway by PI3K-AKT was required for the differentiation of muscle cells and provides the first cellular process exhibiting cross-talk signaling between these two pathways. PI3K-AKT inhibition of Raf-MAPK signaling is also required for vascular smooth muscle and intestinal epithelial cell differentiation (Reusch et al, 2001; Laprise et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Serine-phosphorylated Raf molecules then become inactivated by binding to the 14-3-3 adaptor protein. [113][114][115] The inhibitory effect of Akt on Raf activity appears to be dependent upon cell type and stage of differentiation 116,117 because some investigators have not observed this effect. Certain differentially expressed mediators may be essential for association of Akt and Raf.…”
Section: Pi3k/akt Signaling and The Bcl-2 Family Of Proteinsmentioning
confidence: 99%